PERAN KOMITMEN NORMATIF DAN MOTIVASI EKSTRINSIK PADA HUBUNGAN ANTARA MUTASI DENGAN KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA SEMARANG CANDISARI - Nugroho, Setyo; Wardoyo, Paulus; Saddewisasi, Wyati; Savitri, Fania Mutiara (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine factors that can improve employee performance at the Semarang Candisari Pratama Tax Service Office. The independent variable in this research is mutation and the dependent variable is employee performance with normative commitment and extrinsic motivation as mediating variables. This research uses quantitative methods using questionnaires to collect the required data. The sample in this study was 72 employees taken using the census sampling method. The analysis used was structural equation model (SEM) analysis using the SmartPLS analysis tool. The results of this research show that mutation and normative commitment have a significant positive effect on employee performance, but extrinsic motivation does not have a significant effect on employee performance. Mutations have also been proven to influence normative commitment and extrinsic motivation. The normative commitment variable functions to mediate the relationship between mutation and employee performance.